2021
DOI: 10.1016/j.clnu.2020.10.023
|View full text |Cite
|
Sign up to set email alerts
|

Association of bioelectric impedance analysis body composition and disease severity in COVID-19 hospital ward and ICU patients: The BIAC-19 study

Abstract: Background: The current severe acute respiratory syndrome coronavirus 2 pandemic is unprecedented in its impact. It is essential to shed light on patient characteristics that predispose to a more severe disease course. Obesity, defined as a BMI>30 kg/m 2 , is suggested to be one of these characteristics. However, BMI does not differentiate between fat mass and lean body mass, or the distribution of fat tissue. The aim of the present study was to assess the body composition of COVID-19 patients admitted to the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
96
2
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(117 citation statements)
references
References 55 publications
(77 reference statements)
4
96
2
1
Order By: Relevance
“…Our observations are consistent with the initial finding of Moonen et al [17], who reported a direct relationship between mortality and PhA in critical patients with COVID-19 but did not determine the cut-off point of PhA as a predictor of mortality. Our results extend this observation and overcome the limitations of limited sample size and short follow-up (28 d) by developing survival curves and PhA cut-off points to predict mortality [17]. Importantly, we demonstrate that a cut-off PhA value (by ROC curve of survival) less than 3.95 is more sensitive prognostic factor in predicting mortality in COVID-19 patients than standard biochemical measurements of inflammation (Table 3, Fig.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Our observations are consistent with the initial finding of Moonen et al [17], who reported a direct relationship between mortality and PhA in critical patients with COVID-19 but did not determine the cut-off point of PhA as a predictor of mortality. Our results extend this observation and overcome the limitations of limited sample size and short follow-up (28 d) by developing survival curves and PhA cut-off points to predict mortality [17]. Importantly, we demonstrate that a cut-off PhA value (by ROC curve of survival) less than 3.95 is more sensitive prognostic factor in predicting mortality in COVID-19 patients than standard biochemical measurements of inflammation (Table 3, Fig.…”
Section: Discussionsupporting
confidence: 91%
“…PhA and SPhA are BIA measurements that are novel options for practical assessment and clinical evaluation of impaired nutritional status and prognosis among hospitalized COVID-19 patients and could potentially contribute to enhanced patient care and clinical outcomes. A recent observational cross-sectional cohort study reported that a lower PhA increased the odds of severe COVID-19 and mortality during a 28-d period [17]. Thus, there is a need to determine the prognostic value of PhA and SPhA among COVID-19 patients during acute infection.…”
Section: Introductionmentioning
confidence: 99%
“…To date, only a few studies have reported on body composition (BC) in COVID-19 patients [ 27 , 28 , 29 ]. In an observational and cross-sectional cohort study from the Netherlands, 54 patients, 30 in the ward and 24 in the Intensive Care Unit (ICU), were investigated.…”
Section: Body Compositionmentioning
confidence: 99%
“…BC was evaluated with bioelectric impedance (BIA). No differences were found related to BC, including fat mass, visceral fat area, and fat-free mass, nor were differences in disease severity found between those at the ward and those in the ICU [ 27 ]. However, according to the BMI data, the population was quite homogeneous.…”
Section: Body Compositionmentioning
confidence: 99%
See 1 more Smart Citation